Indonesian Skin Care Stores' Emotional Marketing - Akhmad Nur Zaroni; Sofia Maulida; Heny Herawati; Syamsu Rijal; Arief Yanto Rukmana (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2023)
The purpose of this study is to determine how Scarlett Skincare Store patronage is influenced by emotional and experiential marketing strategies. With a sample of 91 clients, the population of this study is all Scarlett Skincare Store patrons. In this study, unintentional sampling is used. Using IBM SPSS 20, multiple linear regression analysis tools (multiple correlation, determination, F test, and t test) were used to conduct a quantitative study of this research. The study's findings demonstrate how consumer psychology, marketing emotions, and experiential marketing affect Indonesia Skincare Store patron loyalty.